Origins of narrative the romantic appropriation of the Bible - Prickett, Stephen 1939-2020 (Cambridge University Press, 1996)
During the late eighteenth century the Bible underwent a shift in interpretation so radical as to make it virtually a different book from what it had been a hundred years earlier. Even as its text was being revealed as neither stable nor original, the new notion of the Bible as a cultural artefact became a paradigm for all literature. In Origins of Narrative one of the world's leading scholars in biblical interpretation, criticism and theory describes how, while formal religion declined, the prestige of the Bible as a literary and aesthetic model rose to new heights: not merely was English, German and French Romanticism steeped in biblical references of a new kind, but hermeneutics and, increasingly, theories of literature and criticism were biblically derived. Professor Prickett reveals how the Romantic Bible became simultaneously a novel-like narrative work, an on-going site of re-interpretation, and an all-embracing literary form giving meaning to all other writing